Short Mood and Feelings Questionnaire for screening children and adolescents for plastic surgery: cross-cultural validation study - Sucupira, Eduardo; Neto, Miguel Sabino; Lima, Edson Luiz de; Dini, Gal Moreira; Brito, Maria José Azevedo de; Ferreira, Lydia Masako (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Patient-reported outcome measurements assessing the emotional state of children and adolescents who seek plastic surgery are important for determining whether the intervention is indicated or not. The aim of this study was to cross-culturally adapt and validate the Short Mood and Feelings Questionnaire (child/adolescent and parent versions) for Brazilian Portuguese, test its psychometric properties and assess the emotional state of children and adolescents who seek plastic surgery. DESIGN AND SETTING: Cross-cultural validation study conducted in a plastic surgery outpatient clinic at a public university hospital. METHODS: A total of 124 consecutive patients of both sexes were selected between September 2013 and February 2014. Forty-seven patients participated in the cultural adaptation of the questionnaire. The final version was tested for reliability on 20 patients. Construct validity was tested on 57 patients by correlating the Short Mood and Feelings Questionnaire (child/adolescent and parent versions) with the Strengths and Difficulties Questionnaire and the Rosenberg Self-Esteem scale. RESULTS: The child/adolescent and parent versions of the Short Mood and Feelings Questionnaire showed Cronbach’s alpha of 0.768 and 0.874, respectively, and had good inter-rater reliability (intraclass correlation coefficient, ICC = 0.757 and ICC = 0.853, respectively) and intra-rater reliability (ICC = 0.738 and ICC = 0.796, respectively). CONCLUSIONS: The Brazilian-Portuguese version of the Short Mood and Feelings Questionnaire is a reproducible instrument with face, content and construct validity. The mood state and feelings among children and adolescents seeking cosmetic surgery were healthy.